Confrontation and Insurgency in Borneo, 1960–90. (July 2019) - Phillips, David
A considerable literature has accumulated on the 'Confrontation' conflict over the formation of Malaysia in the mid-1960s. Many accounts are of variable quality, especially where they lack knowledge of the local political and social context or ignore the complexity of often intertwined events. Conclusions from such limited studies can be misleading. This article identifies some aspects of the conventional narrative that should be revisited, particularly the crucial role of the related anti-colonial insurgency and its social and economic roots, the dynamics of the Indonesian intervention and the wider historical context in which the conflict should be placed. Despite British claims of military success and undoubted logistical and diplomatic achievement, Confrontation was in many respects a 'phoney war'. Nevertheless, the Borneo conflict had far-reaching consequences, as well as providing valuable lessons in the development and containment of insurgency. It secured the establishment of Malaysia. It accelerated Britain's withdrawal from its long imperial presence 'East of Suez', while confirming American dominance for the next 50 years of one of the world's strategic keypoints. It underpinned the development of authoritarian government in democratic guise. Hence it eased the way to the devastation of the Borneo rainforest with still incalculable global consequences.